Understanding God"s (im)mutability and (im)passibility: A Greek patristic point of view - Streza, Ciprian Ioan (HTS teologiese studies, 2024)
The purpose of this article is to demonstrate that patristic theology has resolved the problem of God’s immutability, which is affirmed paradoxically Holy Scripture. This resolution has been achieved through clarifying of the distinction between God’s essence and his uncreated energies. The Eastern Fathers successfully synthesized key theological concepts: the changelessness of God and his dynamic activity in relation to creation. This synthesis is most profoundly articulated in the Palamite doctrine of the uncreated energies. These energies, while emanating from the changeless essence of God, are nevertheless subject to change. According to this teaching, God is a Trinity of Persons who exists on two primary planes: within himself and in his self-revelation, both in the realms of Theologia and Economia. He is unchangeable in essence, yet changeable, alive, active, and ever-new in his providential action of saving the world through his energies. Because he is transcendent, he can be immanent, instilling in the souls who love him a deeper thirst to know and experience him more profoundly.Contribution: The dogmatic formulas in Eastern Christianity are apophatic, antinomic and paradoxical because they encompass essentially contradictory aspects of a living and inexhaustibly rich reality. Thus, by their very nature, dogmas express everything: the infinite and the finite united – without losing their own being in all their dimensions.